Proses Pengelolaan Informasi Organisasi Genbi UNSIKA dalam Mensosialisasikan QRIS - Deni Koesnaedi; Firdaus Yuni Dharta; Rastri Kusumaningrum (Economic Reviews Journal, 2025)
QR Code Indonesia Standard (QRIS) is an innovative digital payment tool created to encourage the digital economy towards the vision of an Indonesian payment system 2025 that is practical, efficient and inclusive. This research aims to find out how the organizational information management process is carried out by the Indonesian New Generation (GenBI) commissariat of Singaperbangsa University Karawang (Unsika) for the 2021/2022 period in socializing QRIS. The method used in this research is to use qualitative methods, data analysis techniques by collecting interview, observation and documentation data. The resource persons in this research are four members of GenBI who are responsible for the QRIS socialization program and one person from BI as an additional informant in organizational information management process. Researchers use Organizational Information Theory by Karl Weick as the main theory. The findings in this research are that GenBI Unsika for the 2021/2022 period implemented 3 stages of reducing uncertainty in processing incoming organizational information during QRIS socialization, including; 1.) Information Reception, 2.) Selection, and 3.) Retention. GenBI Unsika also uses two organizational communication processes according to Onong Effendy, namely formal and informal communication processes.